Seasonal and inter-annual variations of gas exchange in thirteen woody species along a climatic gradient in the Mediterranean island of Mallorca - Gulías, J.; Cifre, J.; Jonasson, S.; Medrano, H.; Flexas, J. (Flora - Morphology, Distribution, Functional Ecology of Plants, 2009)
We studied the inﬂuence of summer drought and winter temperatures on seasonal and spatial variations of lightsaturated net photosynthesis and stomatal conductance in Mediterranean woody species. We measured variations in leaf gas exchange over 3 years in 13 Mediterranean trees and shrubs, located at four different sites along a climate gradient of temperature and precipitation in the island of Mallorca (West Mediterranean basin). Net photosynthesis and stomatal conductance were at a maximum during spring, autumn or winter and at a minimum during summer in most sites, species and years. Nevertheless, important spatial, temporal and species-speciﬁc variations were observed. Summer drought limitation to gas exchange was greatest in the dry part of the transect, where many species showed their maximum gas exchange rate during winter. In contrast, winter temperatures limited gas exchange of many species at the wet and cool end of the transect, while summer depression of gas exchange was shorter and less pronounced. These results suggest that the effect on carbon ﬁxation and productivity by the predicted future increase of aridity in the Mediterranean basin will depend on whether gas exchange is mostly limited by summer drought or by low winter temperatures.
Keywords: evergreen sclerophyllous species; Mediterranean shrubs; Mediterranean trees; photosynthesis; summer drought